Adaptive control for synchronization of semi‐linear complex spatio‐temporal networks with time‐invariant coupling delay and time‐variant coupling delay. (10th August 2022) - Yang, Chuanhai; Yang, Yuqian; Yang, Chengdong; Zhu, Jie; Zhang, Ancai; Qiu, Jianlong
Summary: This article studies the adaptive control for synchronization of semi‐linear complex spatio‐temporal networks (CSNs). And the leader‐following and leaderless CSN with time‐invariant coupling delay and time‐variant coupling delay are developed separately from two aspects. The adaptive control strategies are proposed to reach the asymptotic convergence of synchronization error. Synchronization criteria and sufficient conditions are obtained for the leader‐following CSN error model and leaderless CSN error model by constructing the apposite Lyapunov–Krasovskii functions and applying Wirtinger's inequality. Finally, two experimental examples are given to verify the feasibility of the theories proposed in this article.